Evaluating the Indonesian VAT policy: evidence from the Indonesian household surveys - Bukit, Irene Santi Beru (2024)
The VAT holds a significant role as the second largest contributor to Indonesia's tax revenue . However, the government must pay attention not only to the tax revenue but also to good tax principles. The four ultimate tax collection principles are fairness, certainty, convenience, and efficiency (Smith, 1776). Fairness is the principle that will be the focus of the present analysis. A tax is considered fair and progressive or proportional when the tax payable is in line with the ability of taxpayers to pay. Unfortunately, the VAT system, as an indirect tax, does not enable the government to treat the taxpayers directly and differently. Therefore, in the VAT system, the most reliable way is to treat the commodities differently.